Preparation method of high-performance gradient denture with sintering consistency

CN117731432BActive Publication Date: 2026-10-27HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311782753.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2026-10-27
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

[0004]本发明要解决现有梯度义齿各功能层之间的烧结温度不一致,难以实现共烧,导致仿生梯度全瓷义齿各功能层间的界面结合强度较差的问题,进而提供一种实现烧结一致性的高性能梯度义齿的制备方法

Benefits of technology

[0015]本发明提供了一种实现烧结一致性的梯度义齿制备方法,通过制备二硅酸锂微晶玻璃(LDGC)和高强度氧化锆陶瓷粉体的混合粉体来满足仿生义齿各部位的力学性能和透度要求的同时,有效地解决了不同陶瓷粉体之间难以低温共烧的问题。随着混合粉体中二硅酸锂微晶玻璃粒径的减小,其比表面积逐渐增大,表面原子数增多,粉体具有更高的表面能,烧结所需的激活能相较于大粒径粉体更小。进一步调控梯度义齿各功能层中二硅酸锂的含量比例,使其具有不同的比表面积和比表面能,实现了梯度义齿各功能层材料的低温共烧一体化,同时提高了梯度义齿的层间结合强度,减少了义齿崩瓷、断裂等现象的产生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117731432B_ABST
    Figure CN117731432B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a high-performance gradient denture with sintering consistency, and relates to a preparation method of a denture. The application aims at solving the problem of poor interface bonding strength between functional layers of a bionic gradient full-ceramic denture due to inconsistent sintering temperatures between the functional layers of an existing gradient denture, and difficulty in realizing co-sintering. The application comprises the following steps: S1, preparation of mixed powder; S2, printing; and S3, debinding and sintering treatment. The application is used for realizing the preparation of the high-performance gradient denture with sintering consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing dentures. Background Technology

[0002] For oral medicine and research professionals, fabricating biomimetic gradient all-ceramic dentures that combine strong mechanical properties with high aesthetic translucency remains a significant challenge. The fabrication process requires different materials and methods depending on the location and function of the denture. Specifically, the incisal edge of the denture needs to be made of a high-translucency ceramic material, while the distal end, closer to the alveolar bone, requires a high-strength ceramic material (typically zirconia and / or alumina ceramics). Early ceramic dentures, however, only possessed high mechanical strength and low translucency, failing to meet both mechanical and aesthetic requirements and prone to excessive wear and gingival swelling during occlusion. Currently, functional gradient all-ceramic dentures typically combine high-strength and high-toughness zirconia and / or alumina ceramics with microcrystalline glass, which has a similar composition and optical translucency to tooth enamel. The mechanical properties and aesthetic translucency required for different functional layers of the gradient denture are achieved by adjusting the mass ratio of high-strength ceramics and microcrystalline glass in the composite material. The incisal edge of an all-ceramic denture requires high translucency of the ceramic material, so a high-quality proportion of microcrystalline glass incorporated into zirconia ceramic is selected as the ceramic material for the incisal layer; the distal end of an all-ceramic denture requires high mechanical strength, so a high-quality proportion of high-strength zirconia ceramic material is selected as the distal layer material.

[0003] Due to the differences in material properties between microcrystalline glass and high-strength ceramics, and the fact that different functional layers are achieved by varying mass ratios of high-strength ceramics and microcrystalline glass, the sintering characteristics differ significantly. Because the sintering temperatures of each functional layer are inconsistent, it is difficult to co-fire a complete biomimetic gradient all-ceramic denture. This results in poor interfacial bonding strength between the functional layers, thus affecting the long-term clinical success rate of biomimetic gradient all-ceramic denture restorations. Therefore, it is difficult to achieve functional gradient all-ceramic denture fabrication simply by adjusting the mass ratio between microcrystalline glass and high-strength ceramics. Summary of the Invention

[0004] This invention aims to solve the problem that the sintering temperature of the functional layers of existing gradient dentures is inconsistent, making co-firing difficult and resulting in poor interfacial bonding strength between the functional layers of biomimetic gradient all-ceramic dentures. Therefore, it provides a method for preparing high-performance gradient dentures that achieves sintering consistency.

[0005] A method for fabricating high-performance gradient dentures that achieve sintering consistency, comprising the following steps:

[0006] I. Preparation of mixed powders:

[0007] ① Mix 3 to 20 parts by weight of high-strength zirconia powder with 80 to 97 parts by weight of micron-sized lithium disilicate microcrystalline glass powder to obtain dental upper layer powder. Then, mix 72 to 78 parts by weight of dental upper layer powder with 10 to 14 parts by weight of UV-curable oligomer, 5 to 7 parts by weight of reactive diluent, 4 to 8.5 parts by weight of dispersant and 0.5 to 1 part by weight of photoinitiator to obtain dental upper layer slurry.

[0008] ② Mix 50-62 parts by weight of high-strength zirconia powder with 38-50 parts by weight of submicron-sized lithium disilicate microcrystalline glass powder to obtain dental mid-layer powder. Then, mix 72-78 parts by weight of dental mid-layer powder with 10-14 parts by weight of UV-curable oligomer, 5-7 parts by weight of reactive diluent, 4-8.5 parts by weight of dispersant and 0.5-1 parts by weight of photoinitiator to obtain dental mid-layer slurry.

[0009] ③ Mix 95-97 parts of high-strength zirconia powder with 3-5 parts of nano-sized lithium disilicate microcrystalline glass powder according to the mass ratio to obtain subdental powder. Then, mix 72-78 parts of subdental powder with 10-14 parts of UV-curable oligomer, 5-7 parts of reactive diluent, 4-8.5 parts of dispersant and 0.5-1 part of photoinitiator according to the mass ratio to obtain subdental slurry.

[0010] II. Printing:

[0011] Using photopolymer 3D printing technology and dental sublayer, dental superlayer, and dental middle layer slurries, the sublayer, middle layer, and superlayer of the tooth are printed sequentially. Then, the tooth is cleaned, dried, and cured to obtain the printed blank.

[0012] III. Degreasing and sintering treatment:

[0013] Under a nitrogen atmosphere, the printed blank is degreased and then sintered to obtain a high-performance gradient denture with consistent sintering.

[0014] The beneficial effects of this invention are:

[0015] This invention provides a method for fabricating gradient dentures that achieves consistent sintering. By preparing a mixed powder of lithium disilicate glass-ceramic (LDGC) and high-strength zirconia ceramic powder, the mechanical properties and permeability requirements of various parts of the biomimetic denture are met, while effectively solving the problem of low-temperature co-firing between different ceramic powders. As the particle size of the lithium disilicate glass-ceramic in the mixed powder decreases, its specific surface area gradually increases, the number of surface atoms increases, and the powder has a higher surface energy, requiring less activation energy for sintering compared to larger particle size powders. Further control of the lithium disilicate content ratio in each functional layer of the gradient denture allows for different specific surface areas and specific surface energies, achieving low-temperature co-firing integration of the functional layer materials. This also improves the interlayer bonding strength of the gradient denture and reduces phenomena such as porcelain chipping and fracture.

[0016] The gradient dentures prepared by the method of this invention have good mechanical strength and interfacial bonding strength, and are suitable for dental restoration and dental implantation.

[0017] Instruction manual illustrations

[0018] Figure 1 The stress distribution diagrams are shown for the biomimetic gradient denture prepared in Example 1 and the non-gradient denture prepared in Comparative Experiment 1. (a) Example 1, (b) Comparative Experiment 1.

[0019] Figure 2 The image shows a physical copy of the biomimetic gradient denture prepared in Example 2.

[0020] Figure 3 This is a schematic diagram of the layered structure of the gradient denture of the present invention. Detailed Implementation

[0021] Specific implementation method one: Combining Figure 3 Specifically, this embodiment describes a method for preparing a high-performance gradient denture that achieves sintering consistency, which is carried out according to the following steps:

[0022] I. Preparation of mixed powders:

[0023] ① Mix 3 to 20 parts by weight of high-strength zirconia powder with 80 to 97 parts by weight of micron-sized lithium disilicate microcrystalline glass powder to obtain dental upper layer powder. Then, mix 72 to 78 parts by weight of dental upper layer powder with 10 to 14 parts by weight of UV-curable oligomer, 5 to 7 parts by weight of reactive diluent, 4 to 8.5 parts by weight of dispersant and 0.5 to 1 part by weight of photoinitiator to obtain dental upper layer slurry.

[0024] ② Mix 50-62 parts by weight of high-strength zirconia powder with 38-50 parts by weight of submicron-sized lithium disilicate microcrystalline glass powder to obtain dental mid-layer powder. Then, mix 72-78 parts by weight of dental mid-layer powder with 10-14 parts by weight of UV-curable oligomer, 5-7 parts by weight of reactive diluent, 4-8.5 parts by weight of dispersant and 0.5-1 parts by weight of photoinitiator to obtain dental mid-layer slurry.

[0025] ③ Mix 95-97 parts of high-strength zirconia powder with 3-5 parts of nano-sized lithium disilicate microcrystalline glass powder according to the mass ratio to obtain subdental powder. Then, mix 72-78 parts of subdental powder with 10-14 parts of UV-curable oligomer, 5-7 parts of reactive diluent, 4-8.5 parts of dispersant and 0.5-1 part of photoinitiator according to the mass ratio to obtain subdental slurry.

[0026] II. Printing:

[0027] Using photopolymer 3D printing technology and dental sublayer, dental superlayer, and dental middle layer slurries, the sublayer, middle layer, and superlayer of the tooth are printed sequentially. Then, the tooth is cleaned, dried, and cured to obtain the printed blank.

[0028] III. Degreasing and sintering treatment:

[0029] Under a nitrogen atmosphere, the printed blank is degreased and then sintered to obtain a high-performance gradient denture with consistent sintering.

[0030] This embodiment divides the tooth from the occlusal surface to the gingiva into three layers: the upper layer, the middle layer, and the lower layer, based on the stress gradient changes of the tooth.

[0031] In this embodiment, micron-sized and submicron-sized lithium disilicate glass crystal powders are prepared by a melting method, and lithium disilicate powders with different particle sizes are obtained by using different ball milling parameters.

[0032] In this embodiment, nanoscale lithium disilicate glass powder with a diameter of 100 nm or less is prepared using the sol-gel method.

[0033] The sintering consistency of the functional layers in biomimetic gradient all-ceramic dentures is a key factor affecting the molding and application of gradient dentures. The sintering temperature can be effectively adjusted by changing the particle size of the ceramic powder. Small-particle-size powders are influenced by surface and small-size effects; they are small in size, have a large specific surface area, high surface energy, and a large number of surface atoms. The activation energy required for sintering between different powder grains is much lower than that for large-particle-size powders, thus achieving densification at lower sintering temperatures.

[0034] The purpose of this embodiment is to provide a method for fabricating graded dentures that integrates mechanical gradient, aesthetic transparency, and low-temperature co-firing. Based on the stress gradient changes in the teeth, the dentures are layered. The mass ratio of lithium disilicate glass-ceramic and zirconia ceramic powder in different functional layers is adjusted according to the layered structure, resulting in a gradient change in the mechanical and aesthetic properties of the all-ceramic denture. Furthermore, by adjusting the particle size of the glass-ceramic in each functional layer, the problem of difficulty in co-firing between ceramic materials with different contents is solved, improving the interfacial bonding force of the biomimetic graded all-ceramic denture. This achieves mechanical gradient, aesthetic transparency, and low-temperature co-firing integration of the materials in each functional layer of the graded denture, resulting in a functional graded denture with superior performance that meets clinical needs.

[0035] The beneficial effects of this embodiment are:

[0036] This embodiment provides a method for fabricating gradient dentures that achieves sintering consistency. By preparing a mixed powder of lithium disilicate glass-ceramic (LDGC) and high-strength zirconia ceramic powder, the mechanical properties and permeability requirements of various parts of the biomimetic denture are met, while effectively solving the problem of low-temperature co-firing between different ceramic powders. As the particle size of the lithium disilicate glass-ceramic in the mixed powder decreases, its specific surface area gradually increases, the number of surface atoms increases, and the powder has a higher surface energy, requiring less activation energy for sintering compared to larger particle size powders. Further control of the lithium disilicate content ratio in each functional layer of the gradient denture allows for different specific surface areas and specific surface energies, achieving low-temperature co-firing integration of the functional layer materials of the gradient denture. This also improves the interlayer bonding strength of the gradient denture and reduces phenomena such as porcelain chipping and fracture.

[0037] The gradient dentures prepared by the method described in this embodiment have good mechanical strength and interfacial bonding strength, and are suitable for dental restoration and dental implantation.

[0038] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: the average particle size of the micron-sized lithium disilicate glass-ceramic powder in step one ① is 0.9 μm to 2 μm; the average particle size of the submicron-sized lithium disilicate glass-ceramic powder in step one ② is 0.35 μm to 0.8 μm; and the average particle size of the nano-sized lithium disilicate glass-ceramic powder in step one ③ is ≤100 nm. Everything else is the same as in Specific Implementation Method One.

[0039] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: the micron-sized lithium disilicate microcrystalline glass powder mentioned in step one ① and the submicron-sized lithium disilicate microcrystalline glass powder mentioned in step one ② are specifically prepared according to the following steps: Weigh out 64-67 parts SiO2, 13-21 parts Li2O, 4-7 parts Al2O3, 5-8 parts K2O, 1.5-2 parts ZnO, 1.8-2.5 parts CaO, and 1 part... 2.2 parts of P2O5 were weighed to obtain the raw material. The weighed raw material was placed in an alumina container and mixed with anhydrous ethanol to obtain a mixed slurry. The mixed slurry was dried using a rotary evaporator. Then, the dried raw material was melted at a temperature of 1350℃~1500℃ for 3h~5h to obtain glass melt. The glass melt was poured into a heat-resistant steel mold and held in a muffle furnace at a temperature of 600℃~950℃ for 1h~6h to obtain a glass matrix. The glass matrix was then heated at a rate of 2℃ / min~6℃. The glass matrix was heated to 800℃~1000℃ at a heating rate of 1200r / min and held at 800℃~1000℃ for 3h~5h. After holding, it was cooled to room temperature and placed in an agate jar. Then, it was ball-milled for 3h~5h at a rotation speed of 1200r / min~1500r / min and a ball-to-material mass ratio of (2~4):1, and sieved to obtain micron-sized lithium disilicate microcrystalline glass powder. Finally, it was ball-milled at a rotation speed of 2000r / min~2400r / min. Under the conditions of 0 r / min and a ball-to-material mass ratio of (3-5):1, ball mill for 5-8 hours, sieve, and obtain submicron-sized lithium disilicate microcrystalline glass powder; the nano-sized lithium disilicate microcrystalline glass powder mentioned in step 1③ is specifically prepared according to the following steps: weigh 66-68 parts of tetraethyl orthosilicate, 11-19 parts of lithium nitrate, 6-9 parts of hydrated aluminum nitrate, 3-7 parts of potassium nitrate, 1.5-2 parts of zinc nitrate, 1.5-2.5 parts of calcium nitrate, and 1-2 parts of...Five parts of triethyl phosphate; dilute nitric acid with a concentration of 2 mol / L to 4 mol / L is added to deionized water at a mass ratio of 1:(5-15) to obtain a mixed solvent. The weighed tetraethyl orthosilicate and triethyl phosphate are added to the mixed solvent and stirred for hydrolysis for 30-120 minutes to form sol A. The total mass ratio of the tetraethyl orthosilicate and triethyl phosphate to the mixed solvent is 1:(1-10). Lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate are added to deionized water and stirred until completely dissolved to obtain solution B. The total mass ratio of the lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate to the deionized water is 1:(1-10). The water mass ratio is 1:(1-3); solution B is added to sol A, and the pH is adjusted to 9-10 with ammonia until a white suspension is produced. The mixture is then thoroughly stirred and placed at 50℃-90℃ for 12-20 hours to obtain a gel. The gel is then dried in an oven at 100℃-120℃ for 40-60 hours, followed by crushing, grinding, and sieving. Finally, the sieved dry gel powder is heated to 550℃-700℃ at a heating rate of 2℃ / min-6℃ / min and calcined at 550℃-700℃ for 1-5 hours to obtain nano-sized lithium disilicate microcrystalline glass powder. Other steps are the same as in specific embodiment one or two.

[0040] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the high-strength zirconia powder mentioned in steps ① to ③ of step one consists of 95 to 97 parts by mass of zirconia ceramic powder and 3 to 5 parts by mass of auxiliary ceramic powder. The auxiliary ceramic is one or a combination of several of the following: chromium oxide, cerium oxide, hafnium oxide, erbium oxide, niobium pentoxide, zinc oxide, iron oxide, titanium oxide, calcium oxide, magnesium oxide, yttrium oxide, neodymium oxide, strontium oxide, and barium oxide; the average particle size of the high-strength zirconia powder mentioned in steps ① to ③ of step one is 0.8 μm to 2 μm. Everything else is the same as in Specific Implementation Methods One to Three.

[0041] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that: the UV-curable oligomers mentioned in steps ① to ③ of step one are all epoxy acrylates; the reactive diluent mentioned in steps ① to ③ of step one is 1,6-ethylene glycol diacrylate; the dispersant mentioned in steps ① to ③ of step one is all BYK111; and the photoinitiator mentioned in steps ① to ③ of step one is all ethyl 2,4,6-trimethylbenzoylphenylphosphonate. Everything else is the same as in Specific Implementation Methods One to Four.

[0042] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One through Five in that: in step two, the printing layer thickness is 50μm to 75μm and the exposure energy is 20mJ / cm². 2 ~30mJ / cm 2Under these conditions, the subdental layer was printed using photopolymer 3D printing technology and subdental slurry, with a printing layer thickness of 75μm to 100μm and an exposure energy of 15mJ / cm. 2 ~25mJ / cm 2 Under the conditions of photopolymerization 3D printing technology and dental mid-layer slurry, a dental mid-layer is printed on the surface of the subcutaneous layer of the tooth. Finally, the printing layer thickness is 100μm to 150μm and the exposure energy is 10mJ / cm. 2 ~20mJ / cm 2 Under the specified conditions, a dental superlayer is printed on the surface of the middle layer of the tooth using photopolymerization 3D printing technology and dental superlayer slurry. Other aspects are the same as in specific embodiments one through five.

[0043] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the cleaning and drying in step two are specifically carried out as follows: Remove the surface slurry using a lint-free cloth, then clean in an ultrasonic water bath with a power of 140W to 350W for 1 to 5 minutes, and finally place in a vacuum drying oven at a temperature of 50℃ to 110℃ for 1 to 2 hours. Everything else is the same as in Specific Implementation Methods One to Six.

[0044] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One through Seven in that the curing process in step two is specifically carried out according to the following steps: at a curing power of 100mW / cm 2 ~200mW / cm 2 Under the specified conditions, cure for 5 to 30 minutes. Other procedures are the same as in specific embodiments one through seven.

[0045] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: the volume ratio of the subdental layer to the middle layer in step two is 1:(1-2); the volume ratio of the upper layer to the middle layer in step two is 1:(1-1.5). Everything else is the same as in Specific Implementation Methods One to Eight.

[0046] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that the degreasing treatment in step three is specifically carried out as follows: Under a nitrogen atmosphere, the degreasing temperature is raised to 600℃ to 800℃ at a heating rate of 0.1℃ / min to 1℃ / min, and then held at 600℃ to 800℃ for 8 hours to 13 hours under a nitrogen atmosphere and at the same temperature; the sintering treatment in step three is specifically carried out at a temperature of 900℃ to 1000℃ for 15 hours to 24 hours. Everything else is the same as in Specific Implementation Methods One to Nine.

[0047] The beneficial effects of the present invention are verified using the following embodiments:

[0048] Example 1:

[0049] A method for fabricating high-performance gradient dentures that achieve sintering consistency, comprising the following steps:

[0050] I. Preparation of mixed powders:

[0051] ① Mix 3 parts by weight of zirconium oxide powder with 97 parts by weight of micron-sized lithium disilicate glass powder to obtain dental upper layer powder. Then, mix 72 parts by weight of dental upper layer powder with 14 parts by weight of UV-curable oligomer, 5 parts by weight of reactive diluent, 8 parts by weight of dispersant and 1 part by weight of photoinitiator to obtain dental upper layer slurry.

[0052] ② Mix 50 parts by weight of zirconium oxide powder and 50 parts by weight of submicron-sized lithium disilicate microcrystalline glass powder to obtain dental mid-layer powder. Then, mix 75 parts by weight of dental mid-layer powder with 12 parts by weight of UV-curable oligomer, 6 parts by weight of reactive diluent, 6.2 parts by weight of dispersant and 0.8 parts by weight of photoinitiator to obtain dental mid-layer slurry.

[0053] ③ Mix 95 parts by weight of zirconium oxide powder with 5 parts by weight of nano-sized lithium disilicate microcrystalline glass powder to obtain subdental powder. Then mix 78 parts by weight of subdental powder with 10 parts by weight of UV-curable oligomer, 7 parts by weight of reactive diluent, 4.5 parts by weight of dispersant and 0.5 parts by weight of photoinitiator to obtain subdental slurry.

[0054] II. Printing:

[0055] With a printing layer thickness of 50μm and an exposure energy of 20mJ / cm² 2 Under the conditions of photopolymerization 3D printing technology and subdental slurry, the subdental layer was printed, and then the printing layer thickness was 75μm and the exposure energy was 15mJ / cm. 2 Under the conditions of photopolymerization 3D printing technology and dental mid-layer slurry, a dental mid-layer is printed on the surface of the sub-dental layer. Then, the printing layer thickness is 100μm and the exposure energy is 10mJ / cm. 2 Under certain conditions, using photopolymer 3D printing technology and dental slurry, the dental slurry is printed on the surface of the middle layer of the tooth, and then cleaned, dried and cured to obtain the printed blank;

[0056] III. Degreasing and sintering treatment:

[0057] Under a nitrogen atmosphere, the printed blank is degreased and then sintered to obtain a high-performance gradient denture with consistent sintering, namely a biomimetic gradient denture.

[0058] The average particle size of the micron-sized lithium disilicate glass powder mentioned in step 1① is 0.9 μm; the average particle size of the submicron-sized lithium disilicate glass powder mentioned in step 1② is 0.35 μm; and the average particle size of the nano-sized lithium disilicate glass powder mentioned in step 1③ is 90 nm.

[0059] The micron-sized lithium disilicate glass-ceramic powder mentioned in step 1① and the submicron-sized lithium disilicate glass-ceramic powder mentioned in step 1② are prepared according to the following steps: 67 parts SiO2, 13 parts Li2O, 7 parts Al2O3, 8 parts K2O, 1.5 parts ZnO, 2.5 parts CaO, and 1 part P2O5 are weighed out in molar amounts to obtain the raw materials. The weighed raw materials are placed in an alumina container and mixed with anhydrous ethanol to obtain a slurry. The slurry is dried using a rotary evaporator. Then, the dried raw materials are melted at 1350℃ for 5 hours to obtain a glass melt. The glass melt is poured into a heat-resistant steel mold and heated at a temperature of... The glass matrix was obtained by holding it in a muffle furnace at 650℃ for 4 hours. The glass matrix was then heated to 800℃ at a heating rate of 2℃ / min and held at 800℃ for 3 hours. After holding, it was cooled to room temperature and placed in an agate jar. It was then ball-milled for 5 hours at a speed of 1200 r / min and a ball-to-material mass ratio of 2:1, and sieved to obtain micron-sized lithium disilicate microcrystalline glass powder. Submicron-sized lithium disilicate microcrystalline glass powder was obtained by ball-milling for 8 hours at a speed of 2000 r / min and a ball-to-material mass ratio of 3:1. All raw materials were sourced from Sinopharm Chemical Reagent Co., Ltd., with a purity of 99.9%.

[0060] The nano-grade lithium disilicate microcrystalline glass powder described in step 1③ is prepared according to the following steps: Weigh out 68 parts by molar amounts of tetraethyl orthosilicate, 11 parts by molar amounts of lithium nitrate, 9 parts by molar amounts of aluminum nitrate hydrate, 7 parts by molar amounts of potassium nitrate, 1.5 parts by molar amounts of zinc nitrate, 2.5 parts by molar amounts of calcium nitrate, and 1 part by molar amounts of triethyl phosphate. First, add 2 mol / L dilute nitric acid to deionized water at a mass ratio of 1:5 to obtain a mixed solvent. Add the weighed tetraethyl orthosilicate and triethyl phosphate to the mixed solvent and stir for 30 minutes to hydrolyze, forming sol A. The total mass ratio of tetraethyl orthosilicate and triethyl phosphate to the mixed solvent is 1:3. Add lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate to deionized water and stir until completely dissolved to obtain... In solution B, the total mass ratio of lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate to deionized water is 1:1. Solution B is added to sol A, and the pH is adjusted to 9.5 with ammonia until a white suspension is produced. The mixture is then thoroughly stirred and placed at 60°C for 20 hours to obtain a gel. The gel is dried in an oven at 100°C for 60 hours, then crushed, ground, and sieved. Finally, the sieved dry gel powder is heated to 550°C at a heating rate of 4°C / min and calcined at 550°C for 5 hours to obtain nano-sized lithium disilicate microcrystalline glass powder. All the above raw materials are from Sinopharm Chemical Reagent Co., Ltd., with a purity of 99.9%.

[0061] The high-strength zirconia powder mentioned in steps ① to ③ consists of 97 parts by mass of zirconia ceramic powder and 3 parts by mass of auxiliary ceramic powder, wherein the auxiliary ceramic is yttrium oxide; the average particle size of the high-strength zirconia powder mentioned in steps ① to ③ is 1.5 μm.

[0062] The UV-curable oligomers mentioned in steps ① to ③ of step one are all epoxy acrylate RJ313, sourced from German Ryzen Chemicals (China) Co., Ltd.; the reactive diluent mentioned in steps ① to ③ of step one is 1,6-ethylene glycol diacrylate; the dispersant mentioned in steps ① to ③ of step one is all BYK111; and the photoinitiator mentioned in steps ① to ③ of step one is all ethyl 2,4,6-trimethylbenzoylphenylphosphonate. Both the dispersant and the photoinitiator are sourced from Aladdin Reagent Co., Ltd., with a purity of 99.9%.

[0063] The cleaning and drying process described in step two is carried out as follows: remove the surface slurry with a lint-free cloth, then clean in an ultrasonic water bath with a power of 190W for 3 minutes, and finally place in a vacuum drying oven at a temperature of 80℃ for 1 hour.

[0064] The curing process described in step two is specifically carried out according to the following steps: at a curing power of 100mW / cm². 2 Under the given conditions, cure for 10 minutes;

[0065] The volume ratio of the subcutaneous layer to the middle layer of the tooth mentioned in step two is 1:1; the volume ratio of the upper layer to the middle layer of the tooth mentioned in step two is 1:1.

[0066] The degreasing process described in step three is carried out in the following steps: Under a nitrogen atmosphere, the degreasing temperature is raised to 800℃ at a heating rate of 0.1℃ / min, and then the temperature is maintained at 800℃ for 13 hours under a nitrogen atmosphere.

[0067] The sintering process described in step three is specifically a sintering process at a temperature of 900℃ for 24 hours.

[0068] Example 2: This example differs from Example 1 in the following ways: In step 1①, 11 parts by weight of high-strength zirconia powder and 89 parts by weight of micron-sized lithium disilicate glass-ceramic powder are mixed to obtain the upper dental layer powder; in step 1②, 56 parts by weight of high-strength zirconia powder and 44 parts by weight of submicron-sized lithium disilicate glass-ceramic powder are mixed to obtain the middle dental layer powder; in step 1③, 96 parts by weight of high-strength zirconia powder and 4 parts by weight of nano-sized lithium disilicate glass-ceramic powder are mixed to obtain the lower dental layer powder; the sintering treatment in step 3 is specifically carried out at a temperature of 950℃ for 19 hours. Everything else is the same as in Example 1.

[0069] Example 3: This example differs from Example 1 in the following ways: In step 1①, 20 parts by weight of high-strength zirconia powder and 80 parts by weight of micron-sized lithium disilicate glass-ceramic powder are mixed to obtain the upper dental layer powder; in step 1②, 62 parts by weight of high-strength zirconia powder and 38 parts by weight of submicron-sized lithium disilicate glass-ceramic powder are mixed to obtain the middle dental layer powder; in step 1③, 97 parts by weight of high-strength zirconia powder and 3 parts by weight of nano-sized lithium disilicate glass-ceramic powder are mixed to obtain the lower dental layer powder; the sintering treatment described in step 3 is specifically performed at a temperature of 1000℃ for 15 hours. Everything else is the same as in Example 1.

[0070] Comparative Experiment 1:

[0071] A method for fabricating high-performance gradient dentures that achieve sintering consistency, comprising the following steps:

[0072] I. Preparation of mixed powders:

[0073] 95 parts by weight of zirconium oxide powder and 5 parts by weight of nano-sized lithium disilicate microcrystalline glass powder were mixed to obtain dental layer powder. Then, 78 parts by weight of dental layer powder were mixed with 10 parts by weight of UV-curable oligomer, 7 parts by weight of reactive diluent, 4.5 parts by weight of dispersant and 0.5 parts by weight of photoinitiator to obtain dental pulp.

[0074] II. Printing:

[0075] With a printing layer thickness of 100μm and an exposure energy of 10mJ / cm² 2 Under the conditions, a whole bionic denture is printed using photopolymer 3D printing technology and dental pulp, and then cleaned, dried and cured to obtain the printed blank;

[0076] III. Degreasing and sintering treatment:

[0077] Under a nitrogen atmosphere, the printed blank is degreased and then sintered to obtain a non-gradient denture.

[0078] The average particle size of the nano-sized lithium disilicate glass powder mentioned in step one is 90 nm.

[0079] The preparation method of the nano-scale lithium disilicate microcrystalline glass powder described in step one is the same as that in Example 1.

[0080] The high-strength zirconia powder mentioned in step one is composed of 97 parts by mass of zirconia ceramic powder and 3 parts by mass of auxiliary ceramic powder, wherein the auxiliary ceramic is yttrium oxide; the average particle size of the high-strength zirconia powder mentioned in steps one to three is 1.5 μm.

[0081] The cleaning and drying process described in step two is carried out as follows: Use isopropanol to clean the excess paste from the surface of the printed blank, and then place it in a vacuum drying oven at 80°C for 1 hour.

[0082] The curing process described in step two is specifically carried out according to the following steps: at a curing power of 100mW / cm². 2 Under the given conditions, cure for 10 minutes;

[0083] The volume ratio of the subcutaneous layer to the middle layer of the tooth in step two is 1:1; the volume ratio of the upper layer to the middle layer of the tooth in step two is 1:1.

[0084] The degreasing process described in step three is carried out in the following steps: Under a nitrogen atmosphere, the degreasing temperature is raised to 800℃ at a heating rate of 0.1℃ / min, and then the temperature is maintained at 800℃ for 13 hours under a nitrogen atmosphere.

[0085] The sintering process described in step three is specifically a sintering process at a temperature of 1400℃ for 13 hours.

[0086] Comparative Experiment 2: This embodiment differs from Embodiment 1 in the following ways: In step 1①, 22 parts by weight of zirconium oxide powder and 78 parts by weight of micron-sized lithium disilicate glass-ceramic powder are mixed to obtain the upper dental layer powder; in step 1②, 65 parts by weight of zirconium oxide powder and 35 parts by weight of submicron-sized lithium disilicate glass-ceramic powder are mixed to obtain the middle dental layer powder; in step 1③, 100 parts by weight of zirconium oxide powder are mixed to obtain the lower dental layer powder; the sintering treatment described in step 3 is specifically carried out at a temperature of 1400℃ for 13 hours. All other aspects are the same as in Embodiment 1.

[0087] Comparative Experiment 3: This embodiment differs from Embodiment 1 in that: the micron-sized lithium disilicate microcrystalline glass powder mentioned in step 1①, the submicron-sized lithium disilicate microcrystalline glass powder mentioned in step 1②, and the nano-sized lithium disilicate microcrystalline glass powder mentioned in step 1③ are all replaced with lithium disilicate microcrystalline glass powder with an average particle size of 5μm; the sintering treatment mentioned in step 3 is specifically carried out at a temperature of 1200℃ for 11 hours. Everything else is the same as in Embodiment 1.

[0088] An axial load of the same magnitude was applied to the bionic dentures prepared in Example 1 and Comparative Experiment 1 to simulate the biting force that occurs when chewing dentures. Figure 1 The stress distribution diagrams are shown for the biomimetic gradient denture prepared in Example 1 and the non-gradient denture prepared in Comparative Experiment 1. (a) is Example 1 and (b) is Comparative Experiment 1. As can be seen from the stress distribution, the gradient denture has a more uniform stress distribution and reduces the generation of stress concentration.

[0089] Figure 2 The image shows a physical picture of the biomimetic gradient denture prepared in Example 2. As can be seen from the figure, by adjusting the appropriate particle size and content of lithium disilicate microcrystalline glass, a biomimetic denture with integrated gradient aesthetic transparency and mechanical gradient can be prepared at a lower sintering temperature.

[0090] The linear light transmittance, bending strength, and fracture toughness of each functional layer of the gradient denture in Example 1 were measured. The bending strength and fracture toughness of dentures prepared in Examples 1 to 3 and Comparative Experiments 1 to 3 were also measured.

[0091] Method for determining linear light transmittance: This study investigates the translucency of ceramic samples, primarily testing their linear light transmittance. A PerkinElmer Lambda 950 UV-Vis spectrophotometer was used, with a test wavelength range of 200 nm to 800 nm.

[0092] Method for determining flexural strength: Dental prosthesis specimens used in the examples and comparative experiments were processed and tested according to the international standard ISO 6872 for dental porcelain. The samples were processed to dimensions of 4.0 mm × 1.2 mm × 25.0 mm, and the flexural strength was measured using the three-point bending method.

[0093] Fracture toughness determination method: Based on fracture mechanics theory, the three-point bending SENB specimen, commonly used in materials fracture mechanics research, is used to measure fracture toughness using the indentation method.

[0094] Table 2 Performance parameters of powders mixed in different proportions for each layer in Example 1 graded denture

[0095]

[0096] Table 3. Stress stratification and composition of composite grout in comparative experiment 2: biomimetic gradient all-ceramic dentures

[0097]

[0098] Table 4 Performance parameters of the samples from Examples 1 to 3 and Comparative Experiments 1 to 3

[0099]

[0100] In Comparative Experiment 2 and Example 1, the particle size of each layer of powder was the same, but the content was different, resulting in different sintering temperatures for the upper, middle, and lower dental layers. The flexural strengths at the optimal sintering temperatures were 176 MPa, 323 MPa, and 845 MPa, respectively. At the same sintering temperature of 1400℃, the flexural strengths of each layer were 72 MPa, 154 MPa, and 845 MPa, respectively. However, the overall strength of the sample co-fired at 1400℃ was only 171 MPa. Therefore, the desired effect of gradient denture fabrication was not achieved.

[0101] In Comparative Experiment 3, while maintaining the LDGC content in each layer, changing the particle size of the LDGC powder in each layer resulted in all particles exceeding the specified range, failing to achieve the effect of lowering the sintering temperature by changing the particle size. The inconsistent sintering temperatures of each layer made co-firing difficult, and the denture sample prepared in Comparative Experiment 3 only achieved a bending strength of 102 MPa.

[0102] Compared with the comparative experiment, the sintering temperature of the green body printed from the mixed powder slurry was lower, and the prepared gradient denture had better mechanical properties and higher interlayer bonding strength between different tooth functional layers. Simultaneously, adjusting the content and particle size of glass-ceramic in each tooth layer effectively solved the problem of co-firing different ceramic materials, achieving low-temperature co-firing integration between glass-ceramic and zirconia ceramic powder, resulting in good mechanical properties and excellent bonding strength between functional layers.

Claims

1. A method for fabricating high-performance gradient dentures with consistent sintering, characterized in that... It is done in the following steps: I. Preparation of mixed powders: ① Mix 3 to 20 parts by weight of high-strength zirconia powder with 80 to 97 parts by weight of micron-sized lithium disilicate microcrystalline glass powder to obtain dental upper layer powder. Then, mix 72 to 78 parts by weight of dental upper layer powder with 10 to 14 parts by weight of UV-curable oligomer, 5 to 7 parts by weight of reactive diluent, 4 to 8.5 parts by weight of dispersant and 0.5 to 1 part by weight of photoinitiator to obtain dental upper layer slurry. The micron-sized lithium disilicate glass powder has an average particle size of 0.9 μm to 2 μm. ② Mix 50-62 parts by weight of high-strength zirconia powder with 38-50 parts by weight of submicron-sized lithium disilicate microcrystalline glass powder to obtain dental mid-layer powder. Then, mix 72-78 parts by weight of dental mid-layer powder with 10-14 parts by weight of UV-curable oligomer, 5-7 parts by weight of reactive diluent, 4-8.5 parts by weight of dispersant and 0.5-1 parts by weight of photoinitiator to obtain dental mid-layer slurry. The submicron-sized lithium disilicate glass microcrystalline powder has an average particle size of 0.35 μm to 0.8 μm; ③ Mix 95-97 parts of high-strength zirconia powder with 3-5 parts of nano-grade lithium disilicate microcrystalline glass powder according to the mass ratio to obtain subdental powder. Then, mix 72-78 parts of subdental powder with 10-14 parts of UV-curable oligomer, 5-7 parts of reactive diluent, 4-8.5 parts of dispersant and 0.5-1 parts of photoinitiator according to the mass ratio to obtain subdental slurry. The nano-sized lithium disilicate microcrystalline glass powder has an average particle size of ≤100nm; The high-strength zirconia powder mentioned in steps ① to ③ has an average particle size of 0.8 μm to 2 μm; II. Printing: With a printing layer thickness of 50μm~75μm and an exposure energy of 20mJ / cm 2 ~30mJ / cm 2 Under these conditions, the subdental layer was printed using photopolymer 3D printing technology and subdental slurry, with a printing layer thickness of 75μm~100μm and an exposure energy of 15mJ / cm. 2 ~25mJ / cm 2 Under the conditions of photopolymerization 3D printing technology and dental mid-layer slurry, a dental mid-layer is printed on the surface of the subcutaneous layer of the tooth. Finally, the printing layer thickness is 100μm~150μm and the exposure energy is 10mJ / cm. 2 ~20mJ / cm 2 Under certain conditions, using photopolymer 3D printing technology and dental slurry, the dental slurry is printed on the surface of the middle layer of the tooth, and then cleaned, dried and cured to obtain the printed blank; The volume ratio of the subdental layer to the middle layer is 1:(1~2); the volume ratio of the upper layer to the middle layer is 1:(1~1.5); III. Degreasing and sintering treatment: Under a nitrogen atmosphere, the printed preform is degreased and then sintered at a temperature of 900℃~1000℃ for 15h~24h to obtain a high-performance gradient denture with consistent sintering.

2. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The micron-sized lithium disilicate glass powder mentioned in step 1① and the submicron-sized lithium disilicate glass powder mentioned in step 1② are specifically prepared according to the following steps: Weigh out 64-67 parts of SiO2, 13-21 parts of Li2O, 4-7 parts of Al2O3, 5-8 parts of K2O, 1.5-2 parts of ZnO, 1.8-2.5 parts of CaO, and 1-2.2 parts of P2O5 by molar proportions to obtain the weighed raw materials. The raw material is placed in an alumina container and moistened with anhydrous ethanol to obtain a slurry. The slurry is dried using a rotary evaporator, and then melted at 1350℃~1500℃ for 3~5 hours to obtain molten glass. The molten glass is poured into a heat-resistant steel mold and held in a muffle furnace at 600℃~950℃ for 1~6 hours to obtain a glass matrix. The glass matrix is ​​then heated at a rate of 2℃ / min~6℃ / min. The temperature is raised to 800℃~1000℃ and held at this temperature for 3h~5h. After holding, it is cooled to room temperature and placed in an agate jar. Then, it is ball-milled for 3h~5h at a speed of 1200r / min~1500r / min and a ball-to-material mass ratio of (2~4):1, and sieved to obtain micron-sized lithium disilicate microcrystalline glass powder. Finally, it is ball-milled at a speed of 2000r / min~2400r / min and a ball-to-material mass ratio of (2~4):

1. Under the condition of a material-to-mass ratio of (3~5):1, ball mill for 5h~8h, sieve, and obtain submicron-sized lithium disilicate microcrystalline glass powder; the nano-sized lithium disilicate microcrystalline glass powder mentioned in step 1③ is specifically prepared according to the following steps: weigh 66 parts~68 parts of tetraethyl orthosilicate, 11 parts~19 parts of lithium nitrate, 6 parts~9 parts of hydrated aluminum nitrate, 3 parts~7 parts of potassium nitrate, 1.5 parts~2 parts of zinc nitrate, 1.5 parts~2.5 parts of calcium nitrate, and 1 part~2 parts of...Five parts of triethyl phosphate; dilute nitric acid with a concentration of 2 mol / L to 4 mol / L is added to deionized water at a mass ratio of 1:(5~15) to obtain a mixed solvent. The weighed tetraethyl orthosilicate and triethyl phosphate are added to the mixed solvent and stirred for hydrolysis for 30 min to 120 min to form sol A. The total mass ratio of the tetraethyl orthosilicate and triethyl phosphate to the mixed solvent is 1:(1~10). Lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate are added to deionized water and stirred until completely dissolved to obtain solution B. The total mass ratio of the lithium nitrate, aluminum nitrate nonahydrate, potassium nitrate, zinc nitrate, and calcium nitrate to the deionized water is 1:(1~10). The mass ratio of water is 1:(1~3); solution B is added to sol A, and the pH is adjusted to 9~10 with ammonia until a white suspension is produced. The mixture is then thoroughly stirred and allowed to stand at 50℃~90℃ for 12h~20h to obtain a gel. The gel is then dried in an oven at 100℃~120℃ for 40h~60h, followed by crushing, grinding, and sieving. Finally, the sieved dry gel powder is heated to 550℃~700℃ at a heating rate of 2℃ / min~6℃ / min and calcined at 550℃~700℃ for 1h~5h to obtain nano-sized lithium disilicate microcrystalline glass powder.

3. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The high-strength zirconia powder mentioned in steps ① to ③ consists of 95 to 97 parts by mass of zirconia ceramic powder and 3 to 5 parts by mass of auxiliary ceramic powder. The auxiliary ceramic is one or a combination of several of the following: chromium oxide, cerium oxide, hafnium oxide, erbium oxide, niobium pentoxide, zinc oxide, iron oxide, titanium oxide, calcium oxide, magnesium oxide, yttrium oxide, neodymium oxide, strontium oxide, and barium oxide.

4. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The UV-curable oligomers mentioned in steps ① to ③ of step one are all epoxy acrylates; the reactive diluent mentioned in steps ① to ③ of step one is 1,6-ethylene glycol diacrylate; the dispersant mentioned in steps ① to ③ of step one is all BYK111; and the photoinitiator mentioned in steps ① to ③ of step one is all ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

5. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The cleaning and drying process described in step two is carried out as follows: remove the surface slurry with a lint-free cloth, then clean in an ultrasonic water bath with a power of 140W~350W for 1min~5min, and finally place in a vacuum drying oven with a temperature of 50℃~110℃ to dry for 1h~2h.

6. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The curing process described in step two is specifically carried out according to the following steps: at a curing power of 100mW / cm². 2 ~200mW / cm 2 Under the specified conditions, cure for 5 to 30 minutes.

7. The method for fabricating a high-performance gradient denture with sintering consistency according to claim 1, characterized in that... The degreasing process described in step three is carried out in the following steps: Under a nitrogen atmosphere, the degreasing temperature is raised to 600℃~800℃ at a heating rate of 0.1℃ / min~1℃ / min, and then the temperature is maintained at 600℃~800℃ for 8h~13h under a nitrogen atmosphere.

Citation Information

Patent Citations

  • Lithium disilicate glass ceramic with color gradient effect and preparation method thereof

    CN114477774A

  • Functional gradient all-ceramic false tooth and additive preparation method thereof

    CN115500974A